Influence of fatigue in the selected kinematic parameters of hurdle clearance in 400 metre race - In search of an accurate training test - lskra, J.; Przednowek, K. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The paper describes a initial study on the effects of fatigue on the selected kinematic parameters of hurdle clearance. Original test involving a hurdles race over 5 hurdles on a curve was used. The analysis concerned clearing the third hurdle in the initial and final (after the 200 m hurdles race) phase of the race. The study analyzed 15 parameters in five phases of hurdle clearance estimated using the particle swarm optimization algorithm. The material was recorded with a 100 Hz industrial camera. The results indicate that the basic parameters in the changes of a hurdling technique influenced by fatigue include: length of the hurdle clearance and landing distance past the hurdle.